2021
DOI: 10.5829/ije.2021.34.07a.07
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Calcined Bentonite Caly Utilization in Cement Mortar using Response Surface Methodology

Abstract: Discovery of alternative to the pozzolanic materials generated from industrial wastes was needed because of its unavailability when the industries was shutdown permanently. This paper deals the optimization of calcined bentonite clay utilization in cement mortar using response surface methodology (RSM). The variables were taken as three levels of calcination temperature (room temperature, 700 0 C and 800 0 C) and seven levels of calcined bentonite (0%, 5%, 10%, 15%, 20%, 25% and 30%). The compressive strength,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Besides these, Valipour et al [124] and Walker and Pavía [22] reported that the compressive strength of concrete with NP increases with decreasing NP particle size. Also, Homayoonmehr et al [151] and Reddy and Reddy [114] 4…”
Section: Effects On Mechanical Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides these, Valipour et al [124] and Walker and Pavía [22] reported that the compressive strength of concrete with NP increases with decreasing NP particle size. Also, Homayoonmehr et al [151] and Reddy and Reddy [114] 4…”
Section: Effects On Mechanical Propertiesmentioning
confidence: 97%
“…Initial and final setting time is used to know the rate of concrete hydration which is crucial in concrete strength development [107]. The employment of NP in concrete increases initial and final setting time with increasing the percentage content of pozzolana [99,[113][114][115]. That is due to prolonging the hydration process that can cause slow stiffening of the concrete mixture [95,116].…”
Section: Effects Of Natural Pozzolana In Concretementioning
confidence: 99%
“…A functional series of advantageous statistical and mathematical methods that are successfully employed to model and optimize the issues and problem related to the engineering field is called RSM. RSM is a technique whose major aim is to enhance and optimize the obtained responses which were affected by different factors related to the input process [19]. Besides, the connections between received responses and the factors related to manageable input are quantified by RSM.…”
Section: *Correspondingmentioning
confidence: 99%
“…In this method, the input variables with more F-value and less P-value (less 5% with 95% confidence level) have the most effect on the output variables. Therefore, they can be selected as the main variables with regard to their roles in the experimental data [2,18]. The ANOVA table for the input and output variable are shown in Table 4.…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%